Inventory management shrinkage and employee anti-theft approaches. (18th July 2011) - Smith, Alan D.; Smith, Amber A.; Baker, David L.
With the advent of the current global recession, many companies are trying to remain competitive and reducing inventory shrinkage, especially through employee theft deterrence, are become more popular. Through multivariate statistical analysis of 212 managerial employees of both service and manufacturing firms from the Pittsburgh metropolitan area, it was found that traditional attitudinal variables, such as degree of trust of co-workers, degree of co-workers loyal to company, and degree of mistrust particular co-worker may not be good predictors of the occurrence of employee theft and determining the effectiveness of management's proactive measures to counter such inventory shrinkage initiatives. It was also found that certain initiatives, such as properly managed audit programs do provide an effective defense against inventory shrinkage, especially employee theft.